Хірургічне лікування пацієнтів із жовчнокам'яною хворобою та метаболічним синдромом - Сироїд, О. М. (Clinical Endocrinology and Endocrine Surgery, 2009)
117 patients with symptomatic gallstone disease were operated in our clinic from January 2007 to July 2008. The metabolic syndrome (MS) was diagnosed in 50 (42.7%) cases. The patients with MS were older than patients without MS. They had more often arterial hypertension, obesity, steatohepatosis and diabetes mellitus. The laparoscopic cholecystectomy was performed in 40 (80.0%) cases with MS and in 58 (86.6%) cases without MS. The operating time was 30-165 (Me=72.5) min at patients with MS and 40 160 (Me=65.0) min at patients without MS. Postoperative complications were diagnosed in 11 (22.0%) and in four (6.0%) cases respectively. The severe postoperative period caused to prolonged hospital stay of patients with cholelithiasis and MS.